Profile of patients with carcinoma breast: a descriptive clinical study - Purushotham, Sapna; Raj, Raghuram (International Surgery Journal, 2016)
Background:Breast cancer is the most common site-specific cancer in women and is the leading cause of death from cancer for women age 40 to 44 years. It accounts for 33% of all female cancers and is responsible for 20% of the cancer related deaths in women. Methods: Data was collected using pre tested semi structured questionnaire after thorough clinical examination. Total sample size was 200 and these patients were selected by non-probability purposive sampling technique. Results:The most common quadrant involved was upper outer quadrant (64%) followed by upper inner quadrant (12%), lower inner quadrant (10%) and central (10%). Highest number of patients had lump size less than 3cms (48%) followed by more than 5 cms (30%). 22% of patients had lump size between 3-5 cms. Conclusions:Breast cancer is primarily a disease of the old age with the peak incidence in the fifth and sixth decades, but in India the disease is seen a decade earlier, probably because of shorter longevity of life in Indian women.